De jornalistas e jornalismo: um estudo sobre o sujeito-jornalista no discurso do ombudsman da Folha de S. Paulo - Rodrigues, Marília Giselda (2008)
This work aims to understand how the media discourse helps to constitute the subjectjournalist and his identity, taking as corpora analysis the ombudsman column of the newspaper Folha de S. Paulo and other texts from different genres because of their relationship with the ombudsman column. The profession is going through profound changes, some of them motivated by new technologies of communication, which cause an uncertain environment about the directions, the profile of journalists and journalism and even its maintenance as a social practice. Journalists and journalism companies seek to consolidate a process of identity construction that ensures its own existence, based on the supposed society necessities for information as well as readers. The contributions of the philosopher Michel Foucault in terms of the subjectivation processes are important in reading the corpus. French Discourse Analysis was used in selecting and analyzing texts. Basing on Maingueneau (1997, 2001, 2005, 2007), we try to study the genre ombudsman column. Concepts like enunciative scene, cenography, ethos, discourse communities and others, from the French linguist, were used at the analyses, and demonstrates that the journalist strives to constitute himself as a collective information mediator as well as a co-enunciator of all the discourses which are in constant conflict in society. Also, it was possible to understand journalists like subjects that cannot exist like the owners of the truth anymore.